Consumption patterns of the middle-income and low-income consumers (consumer research) / Kimmy Khoo Poh Kim - Kimmy Khoo , Poh Kim (1986)
This graduation exercise is a case study of a comparison of the consumption patterns between the middle-income and low-income consumers in Bangsar. The aim of the study is to find out the differences in type of monthly expenditure and major durable owned by the low-income and middle-income consumers. In order to provide a clear and systematic picture, this study is arranged into various chapters. Chapter I gives a general introduction of the objective and significance of the study. It also discusses the research methodology used and the problems encountered during the fieldwork. Chapter II presents the definition of some concepts and theories in an effort to relate the essential understanding of consumption patterns. It also presents the types of consumption behaviour. Chapter III deals with the factors to be considered in determining the type of consumption activities pursued. It also touches on various aspects of education, financial status, income allocation and material well-being of the consumers which effect the consumer consumption patterns. Chapter IV gives a deeper understanding on the consumers consumption patterns on food and monthly expanses. It illustrates and explains the factors influencing the consumer consumption patterns. Chapter V attempts to describe the demand for consumption of major durable. It describe the demand for consumption of major durable. It describes and explain the relationship of the consumption patterns with income, budget, status and social standing of the consumers. In this an attempt is made to show these factors cause the difference in consumption patterns. Hire purchase and credit installment are also discussed to illustrate how the consumers purchase their major durable and the consequences of using such method of purchase. Finally, the conclusion analysis the findings and implication of the study. A review and recommendation put forth by the writer.